Connecting the past and the future: Academic geographical (im)mobility of Chinese women academics throughout doctoral education - Bao, Li (Frontiers in Psychology, 2022)
Academic geographical mobility is perceived as critical to academic excellence, but it is a gendered terrain. This study seeks to explore the performances of Chinese women academics, shaped by gender norms, on academic geographical (im)mobility throughout their doctoral education in retrospect. To unpack this issue, driven by the Butlerian theoretical concept of “a stylized repetition of acts”, this article analyzes the qualitative data from semi-structured interviews with seven Chinese women academics to investigate their decisions of academic geographical mobility when they were receiving doctoral education, based on contested discourses of the Chinese traditional culture and the advantages academic geographical mobility may bring to their career advancement. This study concludes that the women academics perform (im)mobility for being women by moving with their husbands and staying for their families, and though these performative acts made them recognizable and understandable in social culture, the gender gap was enhanced before academic career begins.